Virtual migration through online freelancing: Evidence from Bangladesh - Bakhtiar, M. Mehrab; Shonchoy, Abu; Meki, Muhammad; Quinn, Simon (University of Oxford, 2021)
Youth unemployment is a major issue in many developing countries, particularly in locations not well connected with large urban markets. A limited number of available job opportunities in urban centres may reduce the benefit of policies that encourage rural–urban migration. In this project, we investigated the feasibility of ‘virtual migration’ by training rural youth in Bangladesh to become online freelancers, enabling them to export their labour services to a global online marketplace. We did this by setting up a ‘freelancing incubator’, which provided the necessary workspace and infrastructure – specifically, high-speed internet connectivity and computers. Close mentoring was also provided to participants to assist in navigating the competitive online marketplace. We show the exciting potential of online work for improving the incomes of poor youth in developing countries. We also highlight the constraints to this type of work: financing constraints for the high training cost, access to the necessary work infrastructure, and soft skills requirements to succeed in the market. We also shed light on some promising possibilities for innovative financial contracts and for ‘freelancing incubators’ or ‘virtual exporting companies’ to assist students in their sourcing of work and skills development.